THE RELATIONSHIP BETWEEN FAMILY SUPPORT IN ELDERLY HYPERTENSIVE ELDERLY WITH COMPLIANCE VISITS TO THE ELDERLY NEIGHBORHOOD HEALTH CENTER IN GUDO JOMBANG - Syaeful Islam; Ahmad Rifai; Anin Wijayanti (STIKES Insan Cendekia Medika Jombang, 2011)
Based on Household Health Surveyin 2007 showed that the prevalence of hypertension reaches0.37%, or 83 per 1,000members of the household. Approximately 0.15% of the number suffered by theelderly. In the elderly who suffer from hypertension requires an appropriate social support, because family support was instrumental in encouraging the elderly interestor willingness to participate in a neighborhood health center. To analyze the relationship between family support in elderly hypertensive elderly with compliance visits to the elderly neighborhood health centerin Gudo Jombang. This study used a cross section alanalyticdesign by taking a sample of 44 people is done by purposive sampling. Testing the data with SPSS version 17.0statistical test